Enhancing Student Participation in Extracurricular Activities Through the Merdeka Curriculum: A Qualitative Study - Sariwani, Desi; Kristiawan, Muhammad; Suherman, Suherman (Journal of Social Work and Science Education, 2025)
This study aims to evaluate the implementation of the Merdeka Curriculum in enhancing student participation in extracurricular activities at SDN 15 Banyuasin III. Using a qualitative approach, data were collected through interviews, observations, and documentation to assess the curriculum's impact on program design, participation factors, implementation challenges, and strategic solutions. The results demonstrate that the Merdeka Curriculum effectively optimizes extracurricular programs, including Traditional Dance, Marching Band, and Scouting, boosting student motivation, character development, and discipline. Key challenges such as limited facilities and scheduling conflicts were addressed through improved coordination, mentor training, and resource allocation. The novelty of this study lies in its focus on the Merdeka Curriculum's role in extracurricular engagement, offering fresh insights into holistic student development. Practical implications include recommendations for schools to strengthen infrastructure and stakeholder collaboration. This research contributes to the discourse on curriculum innovation by highlighting the importance of extracurricular integration in fostering active, well-rounded learners under the Merdeka Curriculum framework. This study provides a model for integrating extracurricular activities in curriculum frameworks.